ШАХСГА ЙЎНАЛТИРИЛГАН ТАЪЛИМДАН ФОЙДАЛАНИШНИНГ ПЕДАГОГИК-ПСИХОЛОГИК ЖИҲАТЛАРИ - Мамбетова, И.Ж. (SCIENCE and SOCIETY, 2016)
The article deals with the advantages and conveniences of the education, oriented to the personality. The person oriented education includes both-teachers‘ and learners‘ activities. One of the most essential principles of the person oriented education is to achieve the unity of cognitive and practical activities in physical and mental development of a person.